2021
DOI: 10.1038/s41467-021-25988-4
|View full text |Cite
|
Sign up to set email alerts
|

Extensive regulation of enzyme activity by phosphorylation in Escherichia coli

Abstract: Protein serine/threonine/tyrosine (S/T/Y) phosphorylation is an essential and frequent post-translational modification in eukaryotes, but historically has been considered less prevalent in bacteria because fewer proteins were found to be phosphorylated and most proteins were modified to a lower degree. Recent proteomics studies greatly expanded the phosphoproteome of Escherichia coli to more than 2000 phosphorylation sites (phosphosites), yet mechanisms of action were proposed for only six phosphosites and fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 72 publications
1
14
0
1
Order By: Relevance
“…The study by Sultan et al in this series supports the recent findings that the bacterial metabolic enzymes are the significant phosphorylation sites by cellular Ser/Thr/Tyr kinases (Schastnaya et al, 2021 ). By employing phosphoproteomic and biochemical approaches, this study has identified impact on the phosphoproteome of Escherichia coli in the absence of hitherto uncharacterized E. coli ser/thr kinase (YeaG).…”
Section: Role Of Ptms In Bacteria In Response To Stress: a Multifunct...supporting
confidence: 85%
“…The study by Sultan et al in this series supports the recent findings that the bacterial metabolic enzymes are the significant phosphorylation sites by cellular Ser/Thr/Tyr kinases (Schastnaya et al, 2021 ). By employing phosphoproteomic and biochemical approaches, this study has identified impact on the phosphoproteome of Escherichia coli in the absence of hitherto uncharacterized E. coli ser/thr kinase (YeaG).…”
Section: Role Of Ptms In Bacteria In Response To Stress: a Multifunct...supporting
confidence: 85%
“…To check whether the above observations are real tendencies for pSTY sites, we replaced every instance of pS by A, pT by V, and pY by F , and predicted the biophysical properties of the modified protein sequence. We observed that the same sequence with modified pSTY > AVF showed an increase in rigidity; all of the values of backbone, disorder, side-chain dynamics, and early fold propensity showed a slight increase in the modified sequence, which illustrates that it is the intrinsic nature of phosphorylatable STY residues to be more dynamic and flexible (Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…To check whether the above observations are real tendencies for pSTY sites, we replaced every instance of pS by A, pT by V and pY by F 70,71 and predicted the biophysical properties for the modified protein sequence. We observed that the same sequence with modified pSTY >AVF showed an increase in rigidity; all the values of backbone, disorder, side chain dynamics and early fold propensity showed a slight increase in the modified sequence, which illustrates that it is the intrinsic nature of phosphorylatable STY residues to be more dynamic and flexible.…”
Section: Resultsmentioning
confidence: 99%
“…P-sites have lower early folding propensities 60 as compared to non-P-sites, indicating that most of the STY residues involved in so-called foldon (protein region that folds as a unit) formation tend not to be phosphorylated (Figure 11D), which fits with their tendency to be buried. To check whether the above observations are real tendencies for pSTY sites, we replaced every instance of pS by A, pT by V and pY by F 70,71 and predicted the biophysical properties for the modified protein sequence. We observed that the same sequence with modified pSTY>AVF showed an increase in rigidity; all the values of backbone, disorder, side chain dynamics and early fold propensity showed a slight increase in the modified sequence, which illustrates that it is the intrinsic nature of phosphorylatable STY residues to be more dynamic and flexible.…”
Section: Biophysical Properties At Sequence Levelmentioning
confidence: 99%